The Muslim world - Stokes, Jamie (New York, NY : Facts on File, 2011)
Examining Muslim communities around the world, this new resource introduces readers to the history, traditions, and great diversity among them. --from publisher description
Focus on the United States -- Global perspectives -- United States documents -- International documents -- How to research the Muslim world -- Facts and figures -- Key players: A to Z -- Organizations and agencies.
Includes bibliographical references (p. 319-341) and index
Keywords: Islamic civilization; Islam -- History; Islamic countries -- History